Novel Approaches to Realize the Reliability of Location Privacy Protocols in Monitoring Wireless Networks - Lilian C. Mutalemwa; Seokjoo Shin (IEEE Access, 2021)
Wireless sensor network (WSN) technology presents significant advantages for Internet of Things (IoT). Sensor-based IoT networks are designed to operate in unattended, harsh, and complex environments. However, WSNs are resource-constrained. Due to the operating environment settings, there exist great challenges in the privacy and reliability of WSN communications. To achieve secure and reliable communications, it is necessary to devise reliable routing protocols and provide a method to evaluate the performance of the protocols. To guarantee location privacy of source nodes, numerous source location privacy (SLP) routing protocols are presented in the literature. However, the existing literature fails to evaluate the SLP reliability of the protocols. This article achieves three main objectives. First, a new relay ring routing (ReRR) protocol is proposed to address some limitations of fake packet-based SLP routing protocols. The routing algorithm of ReRR is specifically designed to provide long-term SLP protection. Second, unlike previous articles that focus solely on measuring the magnitude of SLP protection using performance metrics such as safety period, capture ratio, attack success rate, and capture probability, this article proposes a novel approach to measure the SLP reliability of the protocols. In the third objective, we conduct a series of experiments to analyze the performance of ReRR and fake packet-based protocols. Using the proposed approach, the SLP reliability of the protocols is evaluated. Experiment results reveal that the proposed ReRR protocol exhibits advantageous performance features. It is observed that the fake packet-based routing protocols achieve strong SLP protection by integrating multiple routing techniques such as packet flooding and random distribution of fake packet traffic. However, the achieved SLP protection is short-term and less reliable. On the other hand, the proposed ReRR protocol employs an energy-efficient routing algorithm to guarantee reliability and long-term SLP protection. In addition, the ReRR protocol ensures improved network lifetime.